Microclimatic Studies of Grasslands In the Arid Zone of North-West India - Rao, G G.S.N; Sastry, A S.R.A.S; Krishnan, A (Annals of Arid Zone, 2016)
Microclimatological studies were carried out for a period of 3 years (1976- 1978) during summer. monsoon and post-monsoon seasons in the grassland sites at Chandan (Jaisalmer). Beechwal (Bikaner) and Palsana (Sikar) in the north-west arid zones of India. The percentage of net to total radiation was higher and the albedo v.alues were the lowest during monsoon seas~n. Radiation interception during monsoon season was the lowest at Palsana grasslands sites compared to Beechwa I and Chandan. The thermal environment of grasslands of Chandan was the highest in all the seasons compared to other sites. Higher surface soil temperature (> 50Â°C) during mid-day hours coupled with higher canopy temperature resulted ill considerable heat losses through long wave radiation.